Analisis Aktivitas Nitrifikasi dari Bakteri yang Diisolasi dari Rumah Burung Walet Menggunakan Metode Spektrofotometri - Palestin Palestin; Siti Gusti Ningrum; Hana Cipka Pramuda Wardhani; Dyan Nugrahadi Sutriatmaja; Charisma Putri Winda (JURNAL KAJIAN VETERINER, 2025)
Nitrifying bacteria are essential in the nitrogen cycle, turning ammonia into nitrite and nitrate, which greatly contributes to the contamination of edible bird's nests in swiftlet houses. This study aims to evaluate the nitrifying activity of bacteria isolated from swiftlet housing environments in Central Kalimantan, Indonesia. A total of 16 environmental pooling samples were obtained from four different environmental sources within the swiftlet houses: faeces (n=4), pond water (n=4), edible bird’s nests (n=4), and soil (n=4). The nitrifying activity of each isolate was examined by measuring nitrite production using a spectrophotometric method and ammonium consumption using a commercial ammonium test kit. The main criteria investigated were the ability of the bacteria to oxidize ammonia to nitrite and their ability to result in ammonium reduction. The findings indicated that all 16 isolates were able to generate nitrite within a range of 4.8 to 24.7 ppm and showed considerable ammonium consumption. Among the sources, the bacteria from soil exhibited higher nitrifying activity compared to those from soil, pond water and bird’s nests. The findings indicate that the swiftlet house environment harbors diverse and active nitrifying bacteria. Furthermore, spectrophotometry method can be used as an initial detection for nitrifying bacteria.